Analysis of Islamic Education Policy in Improving the Profesionalism of Islamic Education Teachers at Elementary School - Sulhan Yus; Silahuddin Silahuddin (Sustainable, 2024)
This study examines the professionalism of Islamic Religious Education (IRE) teachers and the implementation of Islamic education policies at SDN Trans Despot Leungah. Islamic education policies are often seen as formalities without proper execution, hindering the achievement of learning objectives. The research aims to explore how these policies impact teacher professionalism. Using a qualitative descriptive approach, data was collected through observation, interviews, and documentation. The results indicate that the professionalism of IRE teachers at SDN Trans Despot Leungah is fairly good, as evidenced by their possession of teacher certifications, relevant qualifications, mastery of teaching materials, effective communication skills, and strong moral character. The implementation of Islamic education policies has been fairly successful, with the school principal actively encouraging teachers to attend seminars (both online and offline) aimed at improving their professionalism, in line with Government Regulation No. 19/2017. This research is limited to an elementary school setting, and further studies are encouraged to expand the exploration of this topic to junior and senior high school institutions.